THE EFFECT OF ECONOMIC GROWTH, LABOR FORCE PARTICIPATION RATE, AND HUMAN DEVELOPMENT INDEX ON POVERTY IN MALUKU (2010-2022): MULTIPLE LINEAR REGRESSION APPROACH - Tipka, Jefri; Ramly, Fahrudin (VARIANCE: Journal of Statistics and Its Applications, 2025)
This study examines the impact of economic growth, labor force participation rate (LFPR), and the human development index (HDI) on poverty in Maluku Province using secondary data from 2010–2022. Employing multiple linear regression via SPSS, the findings indicate that all three variables significantly affect poverty levels. Inclusive economic growth and higher LFPR tend to reduce poverty when aligned with quality job creation. Improvements in HDI reflecting better health, education, and living standards also contribute to poverty reduction. These results underscore the need for targeted and effective poverty alleviation strategies by both regional and national governments.